Bovine Parathyroid Hormone: Amino Acid Sequence - Brewer, H. Bryan (1970)
Bovine parathyroid hormone has been isolated in homogeneous form, and its complete amino acid sequence determined. The bovine hormone is a single chain, 84 amino acids long. It contains amino-terminal alanine, and carboxyl-terminal glutamine. The bovine parathyroid hormone is approximately three times the length of the newly discovered hormone, thyrocalcitonin, whose action is reciprocal to parathyroid hormone.